Study on a simplified model of a high‐rise shear‐type building for evaluation of Q–Δ resonance - Ryosuke Anamizu; Masayuki Kohiyama (Japan Architectural Review, 2023)
Abstract To evaluate Q–Δ resonance, which is a torsional resonance phenomenon caused by geometric nonlinearity, a simplified model for a multistory non‐eccentric building with a shear‐type structure was proposed. A four‐story small‐scale specimen was designed and fabricated, assuming a non‐eccentric steel structure with a height of 324 m, and conducted shaking table tests of the specimen. Q–Δ resonance was confirmed as predicted by the simplified model. In addition, the simplified model reproduced the resonance amplitude calculated using a finite element model of the specimen with constrained out‐of‐plane slab rotation. The simplified model can be used to predict the Q–Δ resonance response when the bending deformation of an entire building is very small.